Microparticle Suspensions and Bacteria-Laden Droplets Are They the Same in Terms of Wetting Signature? - M, Kiran Raj (Langmuir : the ACS journal of surfaces and colloids, 2021)
Adhesion behavior of microbial pathogens on commonly encountered surfaces is one of the most pertinent questions now. We present the characterization of bacteria-laden droplets and quantify the adhesion forces on highly repellent surfaces with the help of a simple experimental setup. Comparing the force signature measured directly using an in-house capillary deflection-based droplet force apparatus, we report an anomalous adhesion behavior of live bacteria (E. coli)-laden droplets on repellent surfaces, which stands in stark contrast to the observed adhesion signature when the doping agent is changed to inert microparticles or the same bacteria in an incapacitated state. We showed that the regular contact angle measurements using optical goniometry is unable to differentiate between the live bacteria and the dead ones (including microparticles) and thus delineate its limitations and the complementary nature of the adhesion measurements in understanding the fundamental interfacial interaction of living organisms on solid surfaces